Urological and sexual function after robotic and laparoscopic surgery for rectal cancer: A systematic review, meta‐analysis and meta‐regression. Issue 1 (17th September 2020) - Wee, Ian Jun Yan; Kuo, Li‐Jen; Ngu, James Chi‐Yong
Abstract: Background: This systematic review sought to compare the urogenital functions after laparoscopic (LAP) and robotic (ROB) surgery for rectal cancer. Methods: This study conformed to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Results: Twenty‐six studies ( n = 2709 for ROB, n = 2720 for LAP) were included. There was a lower risk of 30‐day urinary retention in the ROB group (risk ratios 0.78, 95% confidence interval [CI] 0.61–0.99), but the long‐term risk was comparable ( p = 0.460). Meta‐regression showed a small, positive relationship between age and risk of 30‐day urinary retention in both the ROB ( p = 0.034) and LAP groups ( p = 0.004). The International Prostate Symptom Score was better in the ROB group at 3 months (mean difference [MD] −1.58, 95% CI −3.10 to −0.05). The International Index of Erectile Function score was better in the ROB group at 6 months (MD 4.06, 95% CI 2.38 – 5.74). Conclusion: While robotics may improve urogenital function after rectal surgery, the quality of evidence is low based on the Grading of Recommendations, Assessment, Development and Evaluation approach.